Critical success factors of quality management for the Singapore shipping industry - Chong, Li Yan (2015)
Quality is valued as a competitive advantage for firms and hence sound quality management policies have to be developed to ensure survival in the long run. As the Singapore shipping industry is closely knitted to the country’s economic growth and with the presence of recurring and new challenges, the industry must strive to improve continuously by integrating quality management (QM) in organisations’ key practices and services. However, current studies on the critical success factors (CSFs) of QM in Singapore maritime industry are insufficient. The objectives of this research are to (1) identify the critical success factors of QM, (2) evaluate the importance of QM (which serves as the main motivation in determining the CSFs), (3) measure the extent of current quality practices in order to determine the impact of the CSFs (i.e. Top Management commitment, Process and People Management) in the industry, (4) investigate the relationship between size of company and People Management, (5) examine the impact of CSFs/quality practices and employee satisfaction on customer satisfaction and (6) validate the interdependency of the CSFs. Drawing out six factors from the Singapore Business Excellence Framework and from past research studies, three CSFs were then identified – Top Management, Process and People. Quantitative (surveys) and qualitative (interviews) methods were adopted to investigate if the identified factors coincide with the factors which have contributed to the success of their QM. Statistical data analysis was conducted based on the obtained 31 survey results. The findings show that QM is important to the industry and this provides a strong motivation for this research to be made. The strong extent of the adoption of the three factors within the QM system of the organisations proves that the identified factors are relevant and important to the success of QM in the industry. In general, there is insignificant relationship between size of company and people management. Hypothesized relationships between people management and customer satisfaction, CSFs and customer satisfaction and employee satisfaction and customer satisfaction have proven to be significant except for the interdependency between the three CSFs. However, the identified industry professionals generally agreed that these three CSFs are strongly interdependent. The discrepancy in this result can be due to the small survey’s sample size, survey respondents and interviewees to be good representatives of the QM knowledge in their organisations, assumptions of companies to be quality conscious and differing definitions of quality. Future research should focus on the impact of the identified factors in specific shipping sectors and also obtaining larger survey samples and interviewees from a range of sectors. Focus group and case studies are possible recommendations to re-explore the interdependency of the identified CSFs.